I know the answer to the equation however i cant seem to get the math to work out. Here is the equation.
x-5/3 - x-4/3 = x-3/2 - (x-2)
I assume,Originally Posted by skittles900
$\displaystyle \frac{x-5}{3}-\frac{x-4}{3}=\frac{x-3}{2}-(x-2)$
The common denominator exists and is 6.
Multiplication by six produces,
$\displaystyle 2(x-5)-2(x-4)=3(x-3)-6(x-2)$
Open,
$\displaystyle 2x-10-2x+8=3x-9-6x+12$
Combine,
$\displaystyle -2=-3x+3$
Subtract from both sides,
$\displaystyle -5=-3x$
Divide,
$\displaystyle x=5/3$
I presume,Originally Posted by skittles900
$\displaystyle \frac{x-5}{2}-\frac{x-4}{3}=\frac{x-3}{2}-(x-2)$
The Commond Denominator exists and is 6.
Multiplication upon the equation produces,
$\displaystyle 3(x-5)-2(x-4)=3(x-3)-6(x-2)$
Thus,
$\displaystyle 3x-15-2x+8=3x-9-6x+12$
Combine,
$\displaystyle x-7=-3x+3$
Add 7,
$\displaystyle x=-3x+10$
Add 3x,
$\displaystyle 4x=10$
Divide by 4,
$\displaystyle x=10/4=5/2=2.5$